2007
DOI: 10.1096/fj.07-8430com
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2Areceptor activation and macrophage‐mediated experimental glomerulonephritis

Abstract: In immune-induced inflammation, leukocytes are key mediators of tissue damage. Since A 2A adenosine receptors (A 2A R) are endogenous suppressors of inflammation, we examined cellular and molecular mechanisms of kidney damage to determine whether selective activation of A 2A R will suppress inflammation in a rat model of glomerulonephritis. Activation of A 2A R reduced the degree of kidney injury in both the acute inflammatory phase and the progressive phase of glomerulonephritis. This protection against acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 67 publications
2
51
1
Order By: Relevance
“…Some studies also demonstrated that A 2A receptor activation may cause suppression of the recruitment of T lymphocytes to the lungs [34,35]. Additionally, increased expression of A 2A adenosine receptors has been described in macrophages during the inflammatory process [36] and has been linked to the suppression of macrophage function and inhibition of immune-associated inflammation [36]. Accordingly, our results demonstrated that inosine controls macrophage access to lung compartments via a mechanism involving A 2A receptors.…”
Section: Discussionsupporting
confidence: 69%
“…Some studies also demonstrated that A 2A receptor activation may cause suppression of the recruitment of T lymphocytes to the lungs [34,35]. Additionally, increased expression of A 2A adenosine receptors has been described in macrophages during the inflammatory process [36] and has been linked to the suppression of macrophage function and inhibition of immune-associated inflammation [36]. Accordingly, our results demonstrated that inosine controls macrophage access to lung compartments via a mechanism involving A 2A receptors.…”
Section: Discussionsupporting
confidence: 69%
“…In C2C12 myotubes, treatment with 1 M AngII did not cause an intracellular calcium spike or phosphorylation of extracellular signal-regulated kinase (ERK; a downstream target of AngII), but in C2C12 infected with an adenovirus encoding AT 1 , 17 AngII stimulated a calcium spike and ERK phosphorylation (Supplemental Figure 1). In L6 cells, we found no expression of AT 2 , AT 1A , or AT 1B receptors by ribonuclease protection assay 18,19 ( Figure 1A). By real-time PCR (RT-PCR), we found no detectable AT 1 receptor mRNA in C2C12 cells, a small amount in gastrocnemius muscle (possibly due to vessels within the muscle) and abundant AT 1 receptor mRNA in mouse vein ( Figure 1B).…”
Section: Skeletal Muscle and Muscle-derived Cells Do Not Express Angimentioning
confidence: 95%
“…Three micrograms of RNA from rat aorta smooth muscle cells and L6 myotubes were used in an RNAse protection assay using the Torrey Pines Biolabs kit (Houston, TX) as described previously. 18,19 Muscle Fiber Size Mouse TA muscles were flash-frozen in embedding medium. Crosssections were fixed in 4% paraformaldehyde at room temperature.…”
Section: Rt-pcrmentioning
confidence: 99%
“…Treatment with an adenosine uptake inhibitor attenuates glomerulonephritis in mice [262]. Activation of A 2A receptors has been proposed as a treatment for macrophagemediated experimental glomerulonephritis ( [100]; see also [85]). In experimental mesangial proliferative glomerulonephritis in the rat (anti-Thy-1 model), there is a pronounced mesangial cell proliferative response leading to glomerular hypercellularity.…”
Section: Nephritismentioning
confidence: 99%